2021
DOI: 10.1080/14760584.2021.1991794
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 subunit vaccine adjuvants and their signaling pathways

Abstract: Introduction: Vaccines are the agreed upon weapon against the COVID-19 pandemic. This review discusses about COVID-19 subunit vaccines adjuvants and their signaling pathways, which could provide a glimpse into the selection of appropriate adjuvants for prospective vaccine development studies. Areas covered: In the introduction, a brief background about the SARS-CoV-2 pandemic, the vaccine development race and classes of vaccine adjuvants were provided. . The antigen, trial stage, and types of adjuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 159 publications
0
30
0
Order By: Relevance
“…As a result, there is currently a therapeutic need to improve the efficacy and safety of vaccines against COVID-19. This has, in turn, reinforced the importance of innovation and the use of better immunostimulants for the production of vaccines that provide better, safe, and long-term immunological protection [ 49 , 116 , 117 , 120 ]. In this context, it has been demonstrated that the protective immunity of certain types of vaccines could be enhanced by the addition or substitution of different adjuvants [ 120 , 121 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, there is currently a therapeutic need to improve the efficacy and safety of vaccines against COVID-19. This has, in turn, reinforced the importance of innovation and the use of better immunostimulants for the production of vaccines that provide better, safe, and long-term immunological protection [ 49 , 116 , 117 , 120 ]. In this context, it has been demonstrated that the protective immunity of certain types of vaccines could be enhanced by the addition or substitution of different adjuvants [ 120 , 121 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of the major drawbacks of subunit vaccines is a lower immunogenicity compared with attenuated vaccines. To enhance the potency of subunit vaccines, use of specific adjuvants and multiple injections are needed [8,9]. Another potential disadvantage of subunit vaccines is their relatively high manufacturing cost, especially if the mammalian expression system is used.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to finding new adjuvants, researchers are also modifying existing adjuvants to increase immune-inducing ability and reduce toxicity. It is known that their modification of the epitope further enhances the immunogenicity of subunit vaccines, increasing stability, halflife, and solubility which collectively increase the Th1 response (Mekonnen et al, 2022).…”
Section: The Types Of Vaccines For Covid-19mentioning
confidence: 99%